Oral health counselling in changing schoolchildren’s oral hygiene habits: a qualitative study - Kasila K, Poskiparta M, Kettunen T, Pietila¨ I. (Blackwell Synergy, 2006)
This study explored oral health counselling concerning changes of oral hygiene habits in 11- to 13-year-old schoolchildren within a theoretical framework of the transtheoretical model and the motivational interview.